Glutamate administration is associated with aggravated atherosclerosis and altered expression of RAPGEF1, OPN, and MYL7 in High-Fat Diet-Fed ApoE⁻/⁻ Mice - Xiuli Cheng; Fanshu Dai; Dilraba Mahmut; Xingya Huang; Qin Wang; Biao Zhang (PLoS ONE, 2026)
Objective This study aims to examine whether oral glutamate administration is associated with accelerated atherosclerosis progression in high-fat diet-fed ApoE ⁻ / ⁻ mice and to identify candidate protein associated with this process. Methods Atherosclerosis (AS) was induced in ApoE ⁻ / ⁻ mice by feeding a high-fat diet (HFD) for three months. The mice were randomly divided into four groups: (1) the AS-GLU group, receiving glutamate with HFD; (2) the AS group, receiving HFD with placebo; (3) the Glu group, receiving glutamate with normal chow; and (4) the Control group, receiving normal chow with a placebo. Atherosclerotic lesions were assessed using Lillie's oil red O staining and histological analysis. LC-MS/MS based proteomics profiling was employed to identify differentially expressed proteins, with subsequent validation by Western blotting and qPCR. Results Glutamate administration alone (Glu group) induced minimal plaque formation. The combination of HFD and glutamate (AS-GLU) was associated with a greater atherosclerotic plaque area compared to HFD alone (AS group). Proteomics identified RAPGEF1, OPN, and MYL7 as proteins whose expression was increased in the AS-GLU group compared to AS group. These associations were confirmed by Western blot and qPCR. Conclusions This study shows that oral glutamate administration, in the context of a high-fat diet in ApoE ⁻ / ⁻ mice, is associated with exacerbated atherosclerosis and increased expression of RAPGEF1, OPN, and MYL7. These proteins represent candidate molecules associated with glutamate exposure, but their causal role remains to be determined. Serum glutamate levels were not significantly elevated, and lipid profile changes may also contribute to the observed associations.